2012
DOI: 10.1038/hr.2012.27
|View full text |Cite
|
Sign up to set email alerts
|

Losartan/hydrochlorothiazide combination vs. high-dose losartan in patients with morning hypertension—a prospective, randomized, open-labeled, parallel-group, multicenter trial

Abstract: on behalf of the MAPPY Study InvestigatorsThe treatment of morning hypertension has not been established. We compared the efficacy and safety of a losartan/ hydrochlorothiazide (HCTZ) combination and high-dose losartan in patients with morning hypertension. A prospective, randomized, open-labeled, parallel-group, multicenter trial enrolled 216 treated outpatients with morning hypertension evaluated by home blood pressure (BP) self-measurement. Patients were randomly assigned to receive a combination therapy of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…Thus, it is suggested that morning SBP reduction is important for UAE reduction, irrespeccacy of these treatments in patients with morning hypertension. 1 The MAPPY study has shown that a losartan/HCTZ combination induces a greater morning SBP reduction, the primary endpoint, than high-dose losartan (-18 mmHg vs. -8 mmHg, P<0.001). With regard to the secondary endpoints, the combination regimen decreased UAE (P<0.05), whereas the high-dose regimen lowered serum uric acid (P<0.001).…”
Section: Morning Sbp Reduction and Uae Reductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, it is suggested that morning SBP reduction is important for UAE reduction, irrespeccacy of these treatments in patients with morning hypertension. 1 The MAPPY study has shown that a losartan/HCTZ combination induces a greater morning SBP reduction, the primary endpoint, than high-dose losartan (-18 mmHg vs. -8 mmHg, P<0.001). With regard to the secondary endpoints, the combination regimen decreased UAE (P<0.05), whereas the high-dose regimen lowered serum uric acid (P<0.001).…”
Section: Morning Sbp Reduction and Uae Reductionmentioning
confidence: 99%
“…1 The institutional review boards or ethics committees of all participating institutions approved the study protocol. All patients gave written informed consent.…”
Section: Study Settingmentioning
confidence: 99%
See 1 more Smart Citation
“…5 Previous studies have documented that the combination of losartan (50 mg) with lowdose HCTZ (12.5 mg) successfully reduced BP in patients with essential hypertension. 6,7 However, there has been no study that tested the hypothesis that selective suppression of an exaggerated morning BP surge leads to a regression of target organ damage and a reduction in subsequent CV events.In this issue of Hypertension Research, Ueda et al 8 reported an interesting clinical study, in which they compared the efficacy and safety of a losartan (50 mg)/HCTZ (12.5 mg) combination and high-dose losartan (100 mg) in patients with morning hypertension or a morning BP surge. 9 Combination therapy induced a greater reduction in the morning systolic BP than did high-dose losartan therapy (131.5±11.5 vs. 142.5 ± 13.6 mm Hg, Po0.001).…”
mentioning
confidence: 99%
“…In this issue of Hypertension Research, Ueda et al 8 reported an interesting clinical study, in which they compared the efficacy and safety of a losartan (50 mg)/HCTZ (12.5 mg) combination and high-dose losartan (100 mg) in patients with morning hypertension or a morning BP surge. 9 Combination therapy induced a greater reduction in the morning systolic BP than did high-dose losartan therapy (131.5±11.5 vs. 142.5 ± 13.6 mm Hg, Po0.001).…”
mentioning
confidence: 99%